التأمين على البطالة في الجزائر - منال غريب; الزهرة سديرة (My University, 2018)
Summary: The issue of unemployment insurance in Algeria has been of great importance for workers who have found themselves and for reasons beyond their control in the face of the sudden loss of their occupancy positions, which has been linked mainly to economic reforms and secretions that have adversely affected both workers and enterprises. Therefore, unemployment insurance in Algeria was a very effective insurance measure and a very important step, or it was found by the public authority, with the aim of balancing the interest of the enterprise by alleviating its burden and maintaining its continuity on the one hand and the interest of the laid-off worker by establishing his protection and social briefing on the other. ..................... ملخص : شكل موضوع التأمين عن البطالة في الجزائر أهمية بالغة بالنسبة للعمال الأجراء الذين وجدو أنفسهم و لأسباب خارجة عن إرادتهم أمام فقدان مفاجئ لمناصب شغلهم و الذي إرتبط أساسا بإصلاحات و إفرازات إقتصادية أثرت سلبا على كل من العمال و المؤسسات على حد سواء . و عليه فإن التأمين على البطالة في الجزائر كان بمثابة إجراء تأميني جد فعال و خطوة جد مهمة أو جدتها السلطة العامة بهدف الموازنة بين مصلحة المؤسسة بتخفيف العبء عنها و المحافظة على إستمراريتها من جهة و مصلحة العامل المسرح بإرساء حمايته و إحاطته اجتماعيا من جهة أخرى . ....................... Résumé : La question de l’assurance chômage en Algérie a été d’une grande importance pour les travailleurs qui se sont retrouvés et pour des raisons indépendantes de leur volonté face à la perte soudaine de leurs postes d’occupation, qui a été principalement liée aux réformes économiques et aux sécrétions qui ont nui aux travailleurs et aux entreprises. Par conséquent, l’assurance chômage en Algérie était une mesure d’assurance très efficace et une étape très importante, ou elle a été trouvée par l’autorité publique, dans le but d’équilibrer l’intérêt de l’entreprise en allégeant sa charge et en maintenant sa continuité d’une part et l’intérêt du travailleur licencié en établissant sa protection et son briefing social d’autre part.